Dramatic Utilization of Close-up in Horror Movies (Al-Academy, 2018)
A cinematic shot is the basis of the film, regardless of the size, angle, or motion of this shot. However, the size of the footage and the process of showing or hiding the scene or cinematic personality has a certain speciality related to the nature of cinematic treatment and the type of the movie especially those characterized by the employment of the close-ups to induce ambiguity or spread the mental image of the dramatic events and this relationship between the close-up and horror films is what prompted the researcher to identify the title of the search as follows: Dramatic utilization of Close-Up in Horror MoviesThe research is divided as follows:The methodological framework included the problem of research, which relied on the following question: What is the drama function of the close-up in horror movies? As far as the importance of research and the need for it, the researcher addressed the necessities and the need to address this subject and then the researcher identified the limits of research and the concluded the chapter by setting a definition of the terms that appeared in the title of the research. The theoretical framework was divided into two sections. The first section was entitled (the snapshot: the sizes and indications), where the familiar shot sizes and the indications of the use and employment of these sizes were studied and then the importance of using the close-up in the silent films and how to use them and the necessities for that were also addressed. The second section (horror movies) dealt with the history of the horror movies and the psychological atmosphere they create in addition to how the elements of the cinematic language is utilized in highlighting the indications that the work maker tries to broadcast.The search procedures included the research methodology, community, tool, and the unit of analysis which is identified by the researcher with the film (Do Not Breathe). The researcher came up with number of findings, conclusions, recommendations, proposals and concluded the research with a list of sources and an abstract in English.